The use of fuzzy measures in estimating the interdependences between academic subjects - Mat Kasim, Maznah; Abdullah, Siti Rohana Goh (2013)
Computing the overall student‘s academic achievements is often done by adding all the scores of the student and dividing the value by the number of subjects.This action means that all subjects are seen as having the same weights or same relative importance.Besides that, the subjects are assumed to be independent with each other which is not true in the real context.This paper focuses on estimating the interactions or interdependencies measures among five main subjects taught in Malaysian primary school s where a result from one case study was used as a basis of the discussion.Five experienced teachers were asked to weigh the importance of the subjects by direct rating method.The results showed that the teachers gave same weight to two subjects, whereas the other three subjects have different weights. Furthermore, one mathematical technique known as lamda (λ)–fuzzy measure was used to compute the interdependencies between the selected subjects.The highest interdependency occurred in pair of mathematics and science subjects and the lowest interaction or interdependency was between Malay Language subjects and English. Even though this result cannot be generalized and is not strange to researchers in the field but this study has succeeded in quantifying the interdependencies among the selected subjects.In future research, the relative weights as well as the interdependencies values are suggested to be considered in computing the overall scores of students‘ academic achievements.By doing so, the overall results would explain the real performance of the students.